Platinum Metals in the Environment - Zereini, Fathi (Springer, 2015)
This edited volume presents new data and insights from the most internationally respected PGE experts, representing a variety of disciplines ranging from chemistry, geochemistry, biology, environmental science to toxicology and environmental health. It builds upon three previous co-edited books published by Springer, Zereini and Alt (Eds.) (1999, 2000 and 2006), incorporating the most recent advances on the topic. The book covers the following topical areas related to PGE: sources and applications, analytical methods, environmental fate, bioavailability and chemical behaviour, use of bioindicators and human exposures and health risk potential.